Large Display User Experience - Robertson, George; Czerwinski, Mary; Baudisch, Patrick; Meyers, Brian; Robbins, Dan; Smith, Greg; Tan, Desney (IEEE Computer Graphics and Applications, 2005)
Large displays offer users signiﬁcant beneﬁts and usability challenges. The authors discuss those challenges along with novel techniques to address these issues.